1987
DOI: 10.1002/1097-0142(19871215)60:12<3001::aid-cncr2820601224>3.0.co;2-8
|View full text |Cite
|
Sign up to set email alerts
|

Characterization and frequency distribution of lymphoreticular infiltrates in axillary lymph node metastases of invasive ductal carcinoma of the breast

Abstract: One hundred and seventy-five axillary lymph nodes containing metastatic deposits from 46 invasive ductal carcinomas of the breast were evaluated histologically and immunohistologically. The study yielded the following results: (1) tumor-infiltrating lymphoreticular cells preferentially accumulated in the stromal bands; the tumor foci generally showed a considerably lower degree of infiltration; (2j in most cases, monocytes/macrophages (Mono 1 +) represented the overwhelming majority of tumoh -infiltrating cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
9
0

Year Published

1993
1993
2020
2020

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(11 citation statements)
references
References 37 publications
2
9
0
Order By: Relevance
“…Most of these immunocompetent cells were not, as expected, located in the epithelial tumor tissue itself but were located in the surrounding connective tissues like the adjacent adipose tissue and the tumor capsule. With these results obtained in mice, we corroborate earlier studies using patient material (Horst and Horny, 1988)10. In addition to the well-explored checkpoint axes controlled by tumor cells acting on lymphocytes, there should be other reasons for this rare in ltration rate of immune competent cells into the tumor tissue itself.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Most of these immunocompetent cells were not, as expected, located in the epithelial tumor tissue itself but were located in the surrounding connective tissues like the adjacent adipose tissue and the tumor capsule. With these results obtained in mice, we corroborate earlier studies using patient material (Horst and Horny, 1988)10. In addition to the well-explored checkpoint axes controlled by tumor cells acting on lymphocytes, there should be other reasons for this rare in ltration rate of immune competent cells into the tumor tissue itself.…”
Section: Discussionsupporting
confidence: 91%
“…Our syngeneic WAP-T-breast cancer mouse model re ects the clinical situation well. In a previous study using clinical breast cancer samples, 30% of the tumor in ltrating immunocompetent cells in ductal carcinoma of the breast were present in the surrounding connective tissue(Horst and Horny, 1988)10, while 40% of these cells were present in our syngeneic mouse tumors. Similarly 25% of the in ltrates were noted directly in the epithelial tumor tissues in our WAP-T breast cancers, while it was 19% in the clinical invasive ductal carcinoma cases.…”
mentioning
confidence: 69%
See 1 more Smart Citation
“…It appears that TAMs are actually required for the tumor to survive [16-19]. Other studies have also reported an overwhelming predominance of TAMs within the TAL population of both primary [12,20,21] and metastatic [22] breast carcinoma. Moreover, positive relationships between the presence of macrophages and lymph node metastasis [23], c-erbB2 [24], and increased expression of urokinase plasminogen activator (uPA) [25] in breast cancer have been reported.…”
Section: Introductionmentioning
confidence: 99%
“…Their reduced capacity to produce NO and lyse tumor cells can be partially reversed by INFγ [58,61] . The results of Lopez and ---1) Monocyte-and macrophage-rich mononuclear infiltrates, frequently observed in primary breast cancers and their metastases, presumably have the same causality [37,38] . 2) Concerning the physiology of GM-CSF in host defense see ref.…”
Section: Relation Between Proliferation Of Phagocytic Cells and Tumormentioning
confidence: 78%